Because of Miss Bridgerton - Quinn, Julia, 1970- (Quinn, Julia, 1970- Bridgerton series, 2016)
Everyone expects Billie Bridgerton to marry one of the Rokesby brothers. The two families have been neighbors for centuries, and as a child the tomboyish Billie ran wild with Edward and Andrew. Either one would make a perfect husband... someday. But sometimes fate has a wicked sense of humor. There is only one Rokesby Billie absolutely cannot tolerate, and that is George. He may be the eldest and heir to the earldom, but he's arrogant, annoying, and she's absolutely certain he detests her. Which is perfectly convenient, as she can't stand the sight of him, either. Because when Billie and George are quite literally thrown together, a whole new sort of sparks begins to fly. And when these lifelong adversaries finally kiss, they just might discover that the one person they can't abide is the one person they can't live without.